Stones and Bones: Catholic Responses to the 1812 Collapse of the Mission Church of Capistrano - Vélez, Karin Anneliese (Material religion, 2017)
This essay delves into the 1812 collapse of the Great Stone Church at California's Mission of San Juan Capistrano and its aftermath to consider how early modern Catholics in the greater Iberian world approached the material remains of ruined churches that contained human victims. Questions explored include how Franciscan missionaries reported and reacted to the calamity, why the casualties were disproportionately Indian and female, and what survivors did with the physical remnants of broken churches. Churches that collapsed on worshippers in Arequipa, Cuzco, Lima and Lisbon prior to 1812 are mustered for comparison. Overall, a pattern emerges of Catholics separating stone from bone in these tragic situations.